KAJIAN PENGGUNAAN ARANG AKTIF TONGKOL JAGUNG SEBAGAI ADSORBEN LOGAM PB DENGAN BEBERAPA AKTIVATOR ASAM - Alfiany, Herlin; Bahri, Syaiful; Nurakhirawati, Nurakhirawati (Univ. Tadulako, 2013)
Research on the activated charcoal, by some acid activators, as an Pb adsorbent has been done. Corncobs as agricultural waste having a huge potential as a material in activated charcoal. It because of easily to be obtained, but also it is containing high levels of elemental carbon (43.42 %) and hydrogen (6.32 %) which calorific value ranging between 14.7 - 18.9 MJ/kg. This study aimed to determine the effect of acid activation on waste corncobs and the levle of lead (II) absorption. Corncob charcoal were activated by soaked for 24 hours in nitric acid and hydrochloric acid. The results showed that the absorption of iodine on activated charcoal by hydrochloric acid (HCl) was 773.85 mg/g , by sulfuric acid (H2SO4) was 665.76 mg/g and by nitric acid (HNO3) was 637.82 mg/g. Charcoal of 14 g had the best absorption (0.508 ppm) compare to other treatments. The best absorption capacity (23.80 % ) was found in 12 grams of charcoal.